Clinical and Radiographic Outcomes of Pediatric Radial Head Fractures - Ryu, Seung Min (Indian J Orthop, 2018)
BACKGROUND: The treatment of pediatric radial head fracture (RHF) is controversial, and the outcome is unpredictable. We aimed to evaluate the long term clinical and radiographic outcomes of patients with pediatric RHF. MATERIALS AND METHODS: 24 patients with pediatric RHFs operated between January 2004 and 2012 were included in this retrospective study. 17 patients had extra articular radial head (EARH) fractures and 7 had intraarticular radial head (IARH) fractures. The Mayo Elbow Performance Score (MEPS), Tibone and Stoltz classification, range of motion (ROM), and carrying angle (CA) were evaluated. The radial head diameter (RHD) and radial head height (RHH), neck shaft angle (NSA), and distance from the radial head to the radial tuberosity (RHRT) were measured and compared with the other side in simple anteroposterior views of elbow radiographs. RESULTS: At the last followup, the mean MEPS was 100 and 97.9 in groups EARH and IARH, respectively. There were no clinically and radiographically significant differences between the groups. The injured elbows showed smaller ROMs than the uninjured elbows in flexion, supination, and pronation with statistically significant differences. However, the injured elbows showed larger extension ranges than the uninjured elbows with a statistical significance (all P = 0.000). CA, RHD, and RHH were higher in the injured elbows than in the uninjured elbows with statistically significant differences (P = 0.006, 0.000, and 0.011) However, NSA and RHRT of both elbows were similar, with no statistically significant difference (P = 0.810 and 0.752). CONCLUSION: All patients with pediatric RHF were satisfied with the long term clinical results. The injured elbows showed restricted ROMs compared with the uninjured elbows; however, the extension range increased.